O Erotykach Franciszka Dionizego Kniaźnina - Rogala, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article presents four erotic poems by Franciszek Dionizy Kniaźnin: Spocznienie, Z Anakreonta, Ognie młodości and Pasterka, together with an editorial compilation. All poems come from the first book of Erotics published in 1779 and the goal underlying their selection was to present the variety of motifs intertwining in this anthology. The book has its direct addressee, namely the mythological Roman goddess of love, and a considerable part of Kniaźnin‘s erotics are dedicated to this emotion in which Cupid, Venus and Nymphs get people entangled. The first book also includes poems translated from Anacreon, Horace, Claudian, Durini or Sappho. These are paraphrases whose prevailing theme is Bacchic. Several poems reflect on the irreversibly passing human existence that cannot be prevented or stopped, or the ideal realm of shepherds governed by the natural impulse of the heart. The poems discussed herein show richness of forms and motifs introduced on the pages of Erotics by Franciszek Dionizy Kniaźnin, scantily discussed before.